2005
DOI: 10.1111/j.1537-2995.2004.04022.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged platelet preservation by transient metabolic suppression

Abstract: Metabolic suppression before storage at 4 degrees C contributes to better preservation of PLT function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 42 publications
(68 reference statements)
6
52
0
Order By: Relevance
“…11,30 We observed some increase in P-selectin and phosphatidyl serine expression on murine platelets after 48 hours of cold storage. In contrast, P-selectin and phosphatidyl serine expression on the cold-stored human platelets were similar to those of platelets stored at RT (Table 3).…”
Section: Discussionmentioning
confidence: 79%
“…11,30 We observed some increase in P-selectin and phosphatidyl serine expression on murine platelets after 48 hours of cold storage. In contrast, P-selectin and phosphatidyl serine expression on the cold-stored human platelets were similar to those of platelets stored at RT (Table 3).…”
Section: Discussionmentioning
confidence: 79%
“…Reduced glycolysis means that glucose remains present in the cold-stored PLTs throughout the 21-day storage period, which is at least 7 days beyond that of the conventionally stored PLTs, thus supporting an extension of the shelf life. Previous studies have also shown that metabolic suppression can result in preservation of PLT function, 50 which may also provide an explanation for the maintenance of aggregation in cold-stored PLTs. In addition, refrigerated storage reduces bacterial growth, 51,52 which is one of the primary reasons that the shelf life of PLTs is so limited.…”
Section: Discussionmentioning
confidence: 96%
“…28,29 To preserve platelet viability and provide optimal hemostatic effectiveness, an important drawback of storage of platelet concentrates at low temperature is the risk of spontaneous platelet activation, so-called coldinduced activation, which was also observed. 30e32 Coldinduced activation might partly explain GF release after storage of platelets at À70 C in the present study.…”
Section: Discussionmentioning
confidence: 98%